The role of the National Innovation Systems Framework in facilitating socio-economic development in Burkina Faso: model and policy practice - Compaore, Eveline Marie Fulbert Windinmi (2016)
Since the 1960s the government of Burkina Faso has consistently sought to implement new development policies to improve the economic and social conditions of its people. Until the end of the 1990s these efforts have been disappointing and unsatisfactory. In the early 2000s there was a shift towards a knowledge-centred development policy and policy makers trusted that it would bring about the sough-after improvements. In 2006 Burkina Faso chose to adopt the National Innovation Systems (NIS) framework as a policy tool to implement this new policy.